MPT0G413, A Novel HDAC6-Selective Inhibitor, and Bortezomib Synergistically Exert Anti-tumor Activity in Multiple Myeloma Cells - Huang, Fang-I; Wu, Yi-Wen; Sung, Ting-Yi; Liou, Jing-Ping; Lin, Mei-Hsiang; Pan, Shiow-Lin; Yang, Chia-Ron (Frontiers in Oncology, 2019)
In multiple myeloma (MM), homeostasis is largely maintained by misfolded protein clearance via the proteasomal and aggresomal pathways. Histone deacetylase 6 (HDAC6) binds polyubiquitinated proteins and dynein motors and transports this protein cargo to the aggresome for further degradation. Accordingly, a combination of an HDAC6 inhibitor and bortezomib (BTZ) could increase ubiquitinated protein accumulation, leading to further apoptosis. Here we evaluated the anti-MM activity of MPT0G413, a novel specific HDAC6 inhibitor, using in vitro and in vivo models. MPT0G413 treatment more significantly inhibited cell growth in MM cells than in normal bone marrow cells. Furthermore, the combination of MPT0G413 and BTZ enhanced polyubiquitinated protein accumulation and synergistically reduced MM viability, increased caspase-3, caspase-8, caspase-9 levels, and cleaved poly (ADP) ribosome polymerase and also inhibited adherence of MM cells to bone marrow stromal cells (BMSC) and reduced VEGF and IL-6 levels and cell growth in a co-culture system. The combination treatment disturbed the bone marrow microenvironment and induced synergic, caspase-dependent apoptosis. Xenograft tumor growth significantly decreased in combination-treated SCID mice. In conclusion, MPT0G413 and BTZ synergistically inhibit MM viability, providing a framework for the clinical evaluation of combined therapies for MM.